2001
DOI: 10.1097/00006534-200111000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment in Children with Single-Suture Craniosynostosis and Plagiocephaly without Synostosis

Abstract: The objective of this study was to determine whether children with nonsyndromic craniosynostosis and plagiocephaly without synostosis demonstrated cognitive and psychomotor delays when compared with a standardized population sample. This was the initial assessment of a larger prospective study, which involved 21 subjects with nonsyndromic craniosynostosis (mean age, 10.9 months) and 42 subjects with plagiocephaly without synostosis (mean age, 8.4 months). Each child was assessed using the Bayley Scales of Infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(74 citation statements)
references
References 18 publications
7
65
1
1
Order By: Relevance
“…10,17,18 Our findings are also consistent with the 2 prospective investigations of the Panchal group, 12,13 which found that none of their sample of infants with DP displayed accelerated functioning in cognition or motor skill development. Because motor development is particularly rapid during this early stage of development, it may be the skill domain that is most vulnerable.…”
Section: Discussionsupporting
confidence: 87%
“…10,17,18 Our findings are also consistent with the 2 prospective investigations of the Panchal group, 12,13 which found that none of their sample of infants with DP displayed accelerated functioning in cognition or motor skill development. Because motor development is particularly rapid during this early stage of development, it may be the skill domain that is most vulnerable.…”
Section: Discussionsupporting
confidence: 87%
“…Findings appear consistent with much of the previous literature, in showing that during the early infancy period and prior to surgical correction of the deformity, infants with craniosynostosis display motor and/or mental developmental abilities within the normal range as a group, although the distribution of scores appear lower than expected. Hence, these infants are more likely to display average to below average performances, and not display accelerated performances in the developmental areas assessed [26][27][28][29][30][31]. Motor skills appear most susceptible to impairment at this developmental phase, with these infants being 2.2 times more likely to display motor developmental delay than the general population.…”
Section: Discussionmentioning
confidence: 98%
“…However, others have shown that these infants perform significantly below normative expectations or control samples [26,27] with higher than expected prevalence of mild to significant delay in cognition [26]. Studies which have addressed motor function have reported significantly lower performances on motor skill abilities on the Bayley scales in untreated patients with mixed forms of singlesuture synostosis compared with normative population estimates or control group samples [26][27][28][29][30]. In fact, motor skills appear to be the area of most significant deficit, with scores in several of these studies falling around the mildly delayed range [28] compared with cognitive scores, which fell typically within normal limits.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10] Unfortunately, the phenomenon of deformational plagiocephaly seems to have been forgotten somewhat in this debate. Most researches have presumed that plagiocephaly without synostosis is not associated with any developmental delays.…”
mentioning
confidence: 99%